2014
DOI: 10.1097/prs.0000000000000417
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of the embrace Advanced Scar Therapy Device to Reduce Incisional Scar Formation

Abstract: Background Scarring represents a significant biomedical burden in clinical medicine. Mechanomodulation has been linked to scarring through inflammation, but until now a systematic approach to attenuate mechanical force and reduce scarring has not been possible. Methods The authors conducted a 12-month, prospective, open-label, randomized, multicenter clinical trial to evaluate abdominoplasty scar appearance following postoperative treatment with the embrace Advanced Scar Therapy device to reduce mechanical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 14 publications
2
60
0
1
Order By: Relevance
“…are also officers of Scarless Laboratories, Inc. ratio of type III to type I collagen. 3,9 However, Phase 3 human clinical trials with recombinant human TGF-b3 (avotermin; Juvista, Renovo, Manchester, UK) 10 and three Phase 2 studies with IL-10 failed to show efficacy in scar reduction. 11,12 In an effort to better identify key factors in scarless fetaltype repair, we used a fetal rat skin model that transitions from fetal-type scarless healing to adult-type repair with scar between embryonic days 16.5 (E16; early gestation) and 18.5 (E18; late gestation) (term, 21.5 days).…”
mentioning
confidence: 99%
“…are also officers of Scarless Laboratories, Inc. ratio of type III to type I collagen. 3,9 However, Phase 3 human clinical trials with recombinant human TGF-b3 (avotermin; Juvista, Renovo, Manchester, UK) 10 and three Phase 2 studies with IL-10 failed to show efficacy in scar reduction. 11,12 In an effort to better identify key factors in scarless fetaltype repair, we used a fetal rat skin model that transitions from fetal-type scarless healing to adult-type repair with scar between embryonic days 16.5 (E16; early gestation) and 18.5 (E18; late gestation) (term, 21.5 days).…”
mentioning
confidence: 99%
“…The Embrace device significantly improved scar appearance ( p = 0.027) according to visual analogue scale scores. 111 Using the Patient and Observer Scar Assessment Scale, both subjects and investigators concluded that Embrace treated scars displayed a significantly improved appearance ( p = 0.02 and p < 0.001, respectively). 111 As each patient served as their own control, the rate at which subjects exited the study likely had little effect on the final outcome.…”
Section: 108mentioning
confidence: 99%
“…111 Using the Patient and Observer Scar Assessment Scale, both subjects and investigators concluded that Embrace treated scars displayed a significantly improved appearance ( p = 0.02 and p < 0.001, respectively). 111 As each patient served as their own control, the rate at which subjects exited the study likely had little effect on the final outcome. However, these results could be skewed if the 11 subjects who did not complete the required 12-month follow-up did so because they did not believe that the Embrace device improved scar appearance.…”
Section: 108mentioning
confidence: 99%
See 1 more Smart Citation
“…There are an estimated 12 million traumatic lacerations treated in the United States emergency rooms each year, 250 million surgical incisions created worldwide every year, and 11 million burns severe enough to warrant medical treatment worldwide. 1,2 In this review, an overview of both established technologies and emerging therapies for scar prevention and management are presented.…”
Section: Scope and Significancementioning
confidence: 99%